2021
DOI: 10.1021/acssuschemeng.1c03307
|View full text |Cite
|
Sign up to set email alerts
|

LNG Supply Chains: A Supplier-Specific Life-Cycle Assessment for Improved Emission Accounting

Abstract: Global trade in liquefied natural gas (LNG) is growing significantly, as is interest in the life-cycle greenhouse gas (GHG) emissions associated with LNG. Most assessments of lifecycle GHG emissions from LNG have employed national or regional average emission estimates; however, there is significant variability in emissions across different suppliers and across the natural gas supply chain. This work describes a framework for compiling supplier-specific GHG emission data for LNG, from the producing well to reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 26 publications
1
30
1
Order By: Relevance
“…To understand the GHG results in context, this study is compared to three recent desk-based studies, Roman-White et al, 7 NETL, 17 and thinkstep, 18 as shown in Figure 4 . All studies assess the life cycle GHG emissions associated with exporting LNG to different locations and included the LNG shipping transport as one part of the supply chain.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To understand the GHG results in context, this study is compared to three recent desk-based studies, Roman-White et al, 7 NETL, 17 and thinkstep, 18 as shown in Figure 4 . All studies assess the life cycle GHG emissions associated with exporting LNG to different locations and included the LNG shipping transport as one part of the supply chain.…”
Section: Discussionmentioning
confidence: 99%
“… Comparison of GHG emissions from LNG shipping with other studies, expressed in kg CO 2equiv /t LNG delivered, using both GWP100 and GWP20 climate metrics for methane. Source: refs ( 7 )( 17 ), and ( 18 ). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations